Case studies in breast cancer - Harnett, Adrian (Greenwich Medical Media Limited, 2002)
The following cases illustrate the diverse management of the very common condition of breast cancer but they all have catches ranging from diagnostic dilemmas to management problems. Cases are sequenced through the book starting with diagnosis, early stage disease through to locally advanced disease, localised metastatic disease and widespread metastatic disease, including palliative care.